PENGARUH KOMPETENSI SDM, AWIG-AWIG, DAN KETAATAN PELAPORAN KEUANGAN TERHADAP PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA DESA - Ni Kadek Dwi Ayu Astini (UNHI Press, 2021)
Fraud is an intentional or an unintentional act committed by someone or group illegally, to get money or assets that may harm other people or agencies. The purpose of the study is to determine the effect of human resource competence, awig-awig and compliance with financial report on the prevention of fraud which occurs in village fund management of the Pupuan district’s village administration of Pupuan District, Tabanan Regency. The purpose sampling method was chosen with a sample size of 104 respondents consisting of the head and members of PTPKD. The data analysis technique was used in this research is Descriptive Statistics, which is Validity and Reliability Test, Classical Assumption Test that was used Normality Test, Multicollinearity and Heteroskedasticity, Multiple Linier Regression, Coefficient of Determination, F-test and t-test. The results showed that the competence of human resources had no significant effect on fraud prevention. awig-awig has positive and significant effect on fraud prevention. Compliance with financial report has a positive and significant effect on fraud prevention. Those mean that the competence of human resources has not been able to prevent the fraud in the village fund management, awig-awig protection and compliance with good financial report can prevent the fraud in the village fund management.